Measurement technique of shock wave pulses at extremely high pressures - FILIPCZYŃSKI, L.; ETIENNE, J.; ŁYPACEWICZ, G.; WASZCZUK, T. (Archives of Acoustics, 1996)
Two methods were developed for measuring the pressure of shock wave pulses generated by lithotriptors: with a piezoelectric foil transducer and a capacitance one. In the study, the properties of a PVDF type foil transducer working in water were analysed. Its sensitivity was determined as a function of frequency. Compliance was gained between measurements and theory. The impacts of fixed metal electrodes, an additional back plastic load and an electric load on the frequency responses were shown. The principle and various design alternatives of a capacitance transducer designed for measuring the extremely high pressure of shock wave pulses in water were presented. A transducer of this type makes it possible to perform absolute measurements. After implementation, the two transducer types were applied for measuring purposes. Their advantages and disadvantages were shown. The pressure of shock wave pulses measured on this basis in a domestic and a foreign lithotriptors were found to be very close to each other. The pulse rise times were approximately the same for the two devices compared.